Income Tax Policy Amidst Covid-19 Pandemic: Quo Vadis Indonesia? - Prianto Budi Saptono; Ismail Khozen (AKRUAL: JURNAL AKUNTANSI, 2022)
Social distancing policies are a common measure taken by many countries worldwide to prevent the spread of Covid-19 cases. However, the consequence is that the income generated by many people is limited and tends to widen inequality. In a similar situation, many governments need more significant spending to save both health and economy. Given the difficult situation for many people, especially in generating income, this study analyzes the international best practice of income tax policies amidst the Covid-19 pandemic. Besides, this study analyzes how the income tax policy in Indonesia responds to the Covid-19 pandemic and its prospects. The research method used to conduct this study is descriptive qualitative. The results show that income tax policies are one of the most crucial matters that countries worldwide can do to deal with the pandemic. These policies vary from tax relief, recovery-oriented stimulus, and tax increases. Concerning the situation in Indonesia, policies need to be directed at evaluating the income tax policies that have been adopted so far. Individual income tax increases in the upper bracket and the introduction of new taxes such as carbon tax may be essential considerations to save the economy and health. However, the government also needs to manage sensitive issues such as corruption to win people's support to recover from the pandemic.